A new species of Cyrtodactylus (Squamata: Gekkonidae) from northern Laos - Nguyen, Truong Quang; Kingsada, Phouthone; Rösler, Herbert; Auer, Markus; Ziegler, Thomas (Zootaxa, 2010)
We describe a new species of the gekkonid genus Cyrtodactylus from northern Laos, based on four specimens from Luang Nam Tha Province. Cyrtodactylus wayakonei sp. n. is distinguished from the remaining bent-toed-geckos by the combination of the following characters: snout-vent length up to 90 mm; 7–8 supralabials; 9–10 infralabials; rostrum bearing smooth scales; 34–45 scales between fifth supralabials; dorsal tubercles smooth or slightly keeled; 17–19 dorsal tubercle rows; ventrolateral folds slightly developed, with large tubercles; 31–35 ventrals; 85–98 scales around midbody; 151–163 scales between mental and cloacal slit; 6–8 precloacal pores in both sexes; precloacal groove lacking; enlarged femoral scales absent; femoral pores lacking; subcaudals somewhat enlarged, broadened; tail tubercles flat, smooth; head and dorsum with blotched to reticulated pattern.